Remodelling of a bacterial immune system as the simple gene editing tool, Crispr-Cas, for food security and human health (Journal of Bangladesh Academy of Sciences, 2022)
The CRISPR system consists of a guide RNA (gRNA) complementary to a target editable DNA sequence and a CRISPR-associated endonuclease (Cas). The gRNA and Cas together form a ribonucleoprotein (RNP) complex. The gRNA guides the Cas enzyme to the precise site for cutting the target DNA. In bacteria, the gRNA leads the endonuclease to the viral DNA for destruction. This ingenious bacterial immune principle has been used to design gRNA to target an organism’s genome at precise locations for gene editing purposes. Gene edits may include deletion or insertion, repression or activation, base, and epigenome editing, or nucleotide replacement. Therefore the CRISPR-Cas system has created the potential for altering genomes of microbes, plants, and animals. The CRISPR-Cas system has now been developed for use in many applications like finding functions of genes, searching for drug targets, diagnostics, crop improvement, and gene therapy.J. Bangladesh Acad. Sci. 45(2); 131-145: December 2021